Seeds of the kingdom: utopian communities in the Americas - Peterson, Anna Lisa (Oxford University Press, 2005)
Residence on earth -- Farm, land, church : Anabaptist agriculture and community -- Promised land : progressive Catholic agrarians in Latin America -- Nature -- Community -- Utopia